Trichodina heterodentata (Ciliophora: Trichodinidae): A new parasite for Piaractus mesopotamicus (Pisces: Characidae) - De Pádua, Santiago Benites [UNESP]; Martins, Maurício Laterca; Carraschi, Silvia Patrícia [UNESP]; Da Cruz, Claudinei [UNESP]; Ishikawa, Márcia Mayumi (Magnolia Press, 2012)
Trichodinids are mobile peritrichous ciliated protozoa, and widely known as ectocommensals and/or parasites of fish and other aquatic organisms. Little is known about the trichodinid fauna in Brazilian fish. This study reports Trichodina het-erodentata Duncan, 1977 as a new parasite for freshwater fish Piaractus mesopotamicus Holmberg, 1887. This is the first record of this trichodinid in southeastern Brazil. Fifty specimens impregnated with 2% silver nitrate and another fifty stained with Giemsa were used for morphometry on the taxonomic characteristics. T. heterodentata in this study is medi-um size, with a disc-shaped body measuring 49.0 to 61.0 ?m, parasitizing the skin, fins and gills of pacu. Measurement comparisons between the present material and other records from different countries are presented. © 2012 Magnolia Press.
Keywords: Aquaculture health; Fish ectoparasite; Trichodinids